ANALISIS YURIDIS TERHADAP PENEGAKAN HUKUM PIDANADALAM MENANGGULANGI TINDAK PIDANA PENIPUAN DENGAN MODUS BISNIS MULTI LEVEL MARKETING (MONEY GAME) - Afni Adelina Simanjuntak; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One of the goals of the Indonesian state is to promote the common good. To realize the creation the general welfare, the government is obliged to provide employment opportunities so that the people are able to meet their needs. Human life can not be separated from the various needs and the fulfillment of these various needs require a relatively large cost, so that someone must work to have income. Job creation is not only sought by the government, but also by the community itself. One form of business created by the community is Usaha Kecil dan Menengah (UKM). One variation of UKM is multi level marketing business. This business is engaged ini products and services. As the problem in this research are, first, what are some form of multi level marketing business classified as criminal fraud? Second, how’s law enforcement in tackling criminal acts of multi level marketing fraud? This research is a normative research.Form of business illegal MLM is divided into three forms, namely pyramid schemes, investment chain letters and binary system. Law enforcement against illegal MLM business scam is still relatively weak. Thisis due to the absence of strong special regulations.Keywords: law enforcement, criminal fraud, multi level marketing